Physical Activity Affects Emotional Intelligence: A Systematic Review - Dinata, Windo Wiria; Yustiana, Yusi Riksa; Andria, Yogi (STAMINA, 2025)
Physical education is an important component of the education curriculum in Indonesia. Not only aims to develop physical fitness, physical education also has a significant role in influencing broader aspects of student development, including emotional intelligence. This study aims to systematically analyze and collate existing scientific evidence on the role of physical education in influencing emotional intelligence. The research method involved selecting relevant research sources from those with predetermined inclusion criteria. A thorough literature search was conducted, followed by data extraction focusing on article title, research design and methods, research objectives and research results. The Scopus database was the main source of the literature search. The results of this study explain that physical education and physical activity have a role in improving emotional intelligence for children, adolescents and adults. It is also inseparable from male and female gender. It is expected for physical education teachers to be able to integrate programs that can improve the emotional intelligence of students in order to better form higher children's emotional intelligence which certainly affects the quality of life in the future.